A new genus and two new species of saccamminid foraminiferans (Protista, Rhizaria) from the deep Southern Ocean - Cedhagen, Tomas; Gooday, Andrew J.; Pawlowski, Jan (Zootaxa, 2009)
We describe two new species of spherical single-chambered (’saccamminid’) foraminifera from the bathyal and abyssal Weddell Sea (Southern Ocean), collected in epibenthic sledge and Agassiz trawl samples obtained during the 2005 ANDEEP III campaign. Both are assigned to Leptammina gen. nov. The new genus is similar in overall test morphology to Saccammina Carpenter, 1869; it is distinguished mainly by its test wall, which is delicate, flexible and composed of fine mineral grains, rather than being rigid and coarsely agglutinated. In Leptammina grisea gen. et sp. nov., the test wall is relatively thick, grayish with a violet tinge and a dull surface; the cytoplasm is dark greenish. In Leptammina flavofusca gen. et sp. nov., the test is yellowish brown, with a very finely, almost transluscent agglutinated wall; the cytoplasm is pale yellowish. Both species have prominent circular apertures. Maximum likelihood phylogenetic analysis of SSU rRNA gene data showed that both species group together with an undescribed shallow-water Antarctic species (“silver saccamminid”) in a very strongly supported clade (100 %). Leptammina grisea gen. et sp. nov. is a relatively uncommon species (29 specimens from 3 stations), found at 1580–4822 m depth in the central and north–western Weddell Sea; Leptammina flavofusca gen. et sp. nov. is common (398 specimens from 4 stations) at depths of 3138–4795 m in the central Weddell Sea and off Kapp Norvegia. Both species are presently known only from ANDEEP III samples.